'Wasting time': migratory trajectories of adolescence among Eritrean refugee girls in Khartoum. Issue 1 (2nd January 2020) - Grabska, Katarzyna
Abstract : Eritrean adolescent girls' migration to Khartoum exposes the interplay between aspiration and desire of becoming an adult linked to a specific geographical location, dreams of being else-where, impossibilities of returning, and realities of uncertainties and being-stuck inbetween. This paper is based on ethnographic fieldwork among Eritrean adolescent refugee girls and young women in Khartoum (2014–2016), who see Sudan as a transit place to an imagined 'better place' elsewhere. Aspirations and desires of moving elsewhere shape the experiences of and the different transitions associated with one's life course. The transition from adolescence to adulthood is of critical importance, where aspirations of being elsewhere and the impossibilities of achieving this goal shape the experiences of 'becoming an adult'. These transitions are also gendered, both in space and across spaces. Using insights from feminist narrative research, I examine how Eritrean refugee girls and young women narrate and experience migration, waiting and transitions in a transitory context of Khartoum. Through hope for mobility and the experience of waiting while faced with protracted uncertainty, I analyse how waithood, personhood and transition to adulthood are experienced.